Perbandingan Prestasi Belajar Ilmu Tajwid Antara Siswa Yang Dari MI & SD Di Darul ‘Ulum Jombang - Luluk firdausiyah, Firdausiyah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Abstrac Learning is a conscious process, directed to achieve the goal to develop the potential to become a man of faith and piety and morality, in harmony with the aim of the science of recitation which is to make students fluent and fluently read and understand the Qur'an so that it can increase the faith and devotion as well as berakhlaqul karimah. In general, student achievement in junior high school is influenced by the background of students in elementary / MI schools. The method used by researchers is observation, documentation, and interviews with the analysis of paired T Test (independent samples T-test). This calculation with SPSS version 18, the results of this study that T arithmetic> F arithmetic so that Ha is accepted and H0 is rejected, there is a difference in the learning achievement of recitation knowledge between students from MI and SD in Darul ‘Ulum. Based on the average orientation of elementary school student achievement is more achievers than students from MI that is 81.04 - 79.96 = 1, 08.